Lactoferrin Supplementation to Prevent Late-Onset Sepsis in Preterm Infants: A Meta-Analysis - Razak, Abdul; Hussain, Asif (American Journal of Perinatology, 2019)
Objective This study aimed to systematically review and meta-analyze the role of lactoferrin supplementation to prevent late-onset sepsis (LOS) in preterm infants.Study Design Database search include PubMed, Web of Science, and Cochrane central for randomized clinical trial (RCTs). The Cochrane Grading of Recommendations Assessment, Development, and Evaluation methodology was used for summarizing the results.Results Ten RCTs involving 3,679 infants were included. Lactoferrin supplementation with or without probiotics decreased all LOS (relative risk [RR]: 0.56; 95% confidence interval [CI]: 0.36–0.86; I2 = 58%; 10 studies; 3,470 subjects; level of evidence [LOE]: low) significantly. Similarly, lactoferrin supplementation without probiotics decreased all LOS (RR: 0.43; 95% CI: 0.29–0.62; I2 = 0%; 8 studies; 1,209 subjects; LOE: moderate) significantly. Lactoferrin supplementation did not significantly reduce necrotizing enterocolitis (RR: 0.62; 95% CI: 0.29–1.33; I2 = 43%; 6 studies; 3,079 subjects; LOE: low), all-cause mortality (RR: 0.74; 95% CI: 0.36–1.53; I2 = 53%; 8 studies; 3,395 subjects; LOE: very low), bronchopulmonary dysplasia (RR: 1; 95% CI: 0.90–1.13; I2 = 0%; 4 studies; 2,570 subjects; LOE: moderate), and threshold retinopathy of prematurity eligible for surgical treatment (RR: 0.61; 95% CI: 0.25–1.51; I2 = 74%; 2 studies; 2,481 subjects; LOE: very low).Conclusion Low to moderate quality evidence suggests that lactoferrin supplementation reduces LOS in preterm infants. Further research is needed to improve the certainty in the evidence.
Keywords: lactoferrin; preterm; low birth weight; sepsis; fungal infection